2D MXenes for Fire Retardancy and Fire‐Warning Applications: Promises and Prospects. (16th December 2022) - Liu, Lei; Feng, Jiabing; Xue, Yijiao; Chevali, Venkata; Zhang, Yubai; Shi, Yongqian; Tang, Long‐Cheng; Song, Pingan
Abstract: Frequent fire disasters have caused massive impacts to the environment, human beings, and the economy. MXene has recently been intensively researched as potential flame retardants to provide passive fire protection for other materials via its physical barrier and catalyzing carbonization effects. In parallel, MXene has also demonstrated a great promise for creating early fire warning sensors, which is an emerging field that has the potential to provide active fire response through its thermoelectric effect. This makes it possible to integrate passive fire retardancy and active fire warning into one MXene‐based fire protection system on demand. However, fulfilling these promises needs more research. Herein, an overview of passive flame‐retardant materials and next‐generation smart fire warning materials/sensors based on MXene and its derivatives is provided. This study reviews their conceptual design, characterization, modification principles, performances, applications, and mechanisms. A discussion of the challenges that need to be solved for their future practical applications and opportunities is also presented. Abstract : This work provides an overview of passive flame‐retardant materials and next‐generation smart fire warning materials/sensors based on MXene and its derivatives, including their conceptual design, characterization, modification principles, performances, applications, mechanisms, challenges, and future perspectives.